The Influence Of Promotional Mix On Visit Interest Tourism To Air Belanda, Saleman Village, Central Maluku District - Rumodar, Jainun Sulfa; Manuputty, Evandro Adolf Willem; Rumalatu, Gilbert A. (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to: 1). This study aims to determine the effect of the promotional mix on the interest in tourist visits to Air Belanda in Saleman Village. 2). To find out the effect of sales promotion on the interest in tourist visits to the Air Belanda tourist attraction, Saleman Village. 3). To find out the development of the promotion mix on the interest of tourist visits to Air Belanda, Saleman Village. This type of research uses qualitative and quantitative research approaches. This research was carried out at the Air Belanda tourist attraction, Saleman Village, Central Maluku district. The objects in this study are tourists who visit and have not visited the Air Belanda tourist attraction in Saleman Village. Sources of data used are primary data and secondary data. Data collection was taken through direct observation, interviews, and distributing questionnaires to managers and visitors totaling 25 respondents. Data analysis was carried out through the stages of editing, classification, scoring and scoring, tabulation and conclusions. The data analysis technique used is validity test, reliability test, classical assumption test, and hypothesis testing, in managing data using SPSS 25 for windows auxiliary software. The results of the analysis obtained based on this study are the Promotional Mix Variables have a significant effect on the interest of tourist visits, where it is known that the advertising sig value affects the interest in tourist visits is 0.245> 0.05 and the T count value is 1.196 < T table 2.079 and the sales promotion sig value has an effect the interest in tourist visits is 0.735 > 0.05 and the T arithmetic value is 0.343 > T table 2.079 while the public relations sig value does not affect the interest in tourist visits seen from the sig value of 0.001 < 0.05 and the calculated T value is 3.884 > T table 2.079. The conclusion of the research shows that the promotion mix (advertising, sales promotion, and public relations) has an effect on the interest in tourist visits.